THE ROLE OF AI IN LANGUAGE LEARNING: INNOVATIONS IN TEACHING AND ACQUISITION (Ilm fan taraqqiyotida raqamli iqtisodiyot va zamonaviy ta'limning o'rni hamda rivojlanish omillari, 2025)
Abstract. Artificial intelligence (AI) is revolutionizing the way languages are taught and learned. By leveraging AI-powered tools and platforms, learners and educators can access personalized and adaptive learning experiences. This article examines the role of AI in language learning, exploring its applications, benefits, and challenges. Key innovations such as intelligent tutoring systems, natural language processing (NLP), and virtual assistants are discussed, highlighting their impact on student engagement and proficiency. The findings demonstrate that AI-driven approaches enhance efficiency, accessibility, and the overall learning experience.